AI-DRIVEN OMNICHANNEL INTEGRATION: REVOLUTIONIZING RETAIL EXPERIENCE IN THE DIGITAL AGE - Sujata Sujeet Dutta (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the transformative role of artificial intelligence (AI) in enabling seamless cross-channel integration within omnichannel retail environments. As consumers increasingly expect unified shopping experiences across digital and physical touchpoints, retailers face the challenge of delivering consistent, personalized interactions. I explore how AI technologies facilitate the flow of customer data and preferences between online and offline channels, enabling real-time inventory management, personalized recommendations, and integrated loyalty programs. Through an analysis of successful implementations, including case studies of Nordstrom and Starbucks, I demonstrate the potential of AI-driven integration to enhance customer experience, increase loyalty, and improve operational efficiency. The article also addresses critical challenges, such as data privacy concerns and implementation complexities, while offering insights into future trends that will shape the evolving landscape of AI-enhanced omnichannel retail. My findings suggest that retailers who successfully leverage AI for seamless channel integration are better positioned to meet the demands of modern consumers and gain a competitive edge in an increasingly digital marketplace.